Explaining ethnic disparities in bachelor's degree participation: evidence from NZ. Issue 7 (3rd July 2019) - Meehan, Lisa; Pacheco, Gail; Pushon, Zoe
ABSTRACT: There are substantial ethnic gaps in higher education in NZ, despite considerable policy effort aimed at this concern. This study uses newly linked administrative data to examine the underachievement of Māori and Pasifika relative to Europeans. We follow a population cohort born between 1990 and 1994 from school through to young adulthood to assess the relative contributions of prior academic performance, socioeconomic status, and parental education to these gaps. Controlling for the relevant covariates narrows the Māori-European gap, and eliminates the Pasifika-European gap in bachelor's degree participation rates. Utilising Fairlie decompositions, we find that school performance is by far the largest contributor to the ethnic gaps. Socioeconomic status and parental education are also pertinent, but less important. Our results suggest that ethnic-based policies aimed at encouraging participation are likely to have a limited effect if used in isolation, and signal the need for policy interventions earlier in the education system.